Clarithromycin affect methane production from anaerobic digestion of waste activated sludge. (10th May 2020) - Huang, Xiaoding; Liu, Xuran; Chen, Fei; Wang, Yali; Li, Xiaoming; Wang, Dongbo; Tao, Ziletao; Xu, Dong; Xue, Wenjing; Geng, Mingyue; Yang, Qi
Abstract: Anaerobic digestion is widely identified as a sustainable technology for the treatment of waste activated sludge (WAS). However, various antibiotics enriched in WAS making the anaerobic digestion process full of uncertainty. This experiment studied the potential impact of a shock load of macrolide antibiotic clarithromycin (CLA) on CH4 production from anaerobic digestion of thermal pretreatments (55 °C, 10 h) WAS. Experimental results showed that the CH4 production rate was significantly suppressed in the existence of CLA during the first 10 days of anaerobic digestion, but gradually recovered thereafter. Although the total cumulative CH4 yield in the presence or absence of CLA showed little difference after 36 days of digestion, the maximal CH4 production rate decreased from 22.3 ± 0.7 mL/(g volatile suspended solids (VSS)·d) to 15.0 ± 0.4 mL/(g VSS·d) with CLA concentration elevated from 0 to 2000 mg/kg total suspended solids. Mechanism investigations showed that CLA had negative effect on the process of hydrolysis, acidogenesis, acetogenesis, homo-acetogenesis and methanogenesis, but its longer-time and more-severely inhibitory effect on acetogenesis and methanogenesis than other process was the main reason for the lower CH4 production rate in the CLA-added reactors. IonS5 TM XL sequencing analysis showed that the relative abundance of typical syntrophic acetogens, such as Syntrophomonas and Syntrophorhabdus, and the methanogens, such as Methanosaeta and the hydrogenotrophic methanogens all increased with the addition of CLA at the later period of digestion. Their changes were consisted with the variations of volatile fatty acids and CH4 in digesters. Graphical abstract: Image 1 Highlights: The CH4 production rate decreased with increasing the clarithromycin concentration. The cumulative CH4 yield was not affected by clarithromycin. The inhibition to acetogenesis and methanogenesis lasted longer than other process. Clarithromycin enhanced the bacteria richness and decreased the archaea diversity.